Regional Economic Integration in the Middle East and North Africa - Rouis, Mustapha (World Bank, Washington, DC, 2014)
Limited integration has stifled the Middle East and North Africa (MENA) region's significant potential for economic growth and job creation. Home to 5.5 percentage of the world's population and 3.9 percentage of the world's Gross Domestic Product (GDP), the region's share of nonoil world trade is only 1.8 percentages. By contrast, countries opting for a liberal trade and investment regime most notably in East Asia have seen significant increases in trade, employment, and per capita income. If petroleum and gas are included, Middle East and North Africa (MENA) is far more integrated in the world economy, with exports accounting for 6.2 percentages of global trade. Oil and gas exports are three-quarters of total MENA's exports.